Penggunaan model pembelajaran creative problem solving untuk meningkatkan kemampuan berpikir kreatif dan motivasi belajar matematika siswa - Yuda Purnama Putra (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2018)
learning motivation is still low, so to overcome these problems required a learning model that is more focused on students to be more active in thinking on the ability to think creatively, one of which is assumed to improve the Creative Problem Solving learning model ( CPS). This study aims to determine the improvement of students ‘creative thinking skills using the Creative Problem Solving (CPS) learning model compared to students who use conventional learning models and want to know students’ learning motivation. The method used in this study is the explanatory sequential type design (mixed method).Theinstrumentusedinthestudents’creativethinkingskillsintheformof a description problem consisting of seven items in addition to that was also strengthened by questionnaire, interview and observation width to support the test results. The population in this study is the eighth grade students of Rajagaluh 3 Junior High School, while the samples taken randomly according to the class are selected in class VIII-E as the experimental class and class VIII-D as the control class. The experimental class was given learning using the Creative Problem Solving (CPS) learning model and the control class was given learning using conventional learningmodels. Data analysis techniques using two average difference test, correlation test. Based on the results of the analysis and results of data processing, it was concluded that theimprovementofstudents’creativethinkingabilitywasbetterinthecontrolclass using conventional learning models compared to the experimental class using Creative Problem Solving (CPS) learning models and better Student Motivation in the control class compared to experimentalclass.Keywords: Creative Problem Solving(CPS), learning model, creative thinking skills and Learning Motivation